PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN AKIDAH AKHLAK DENGAN METODE INTERAKTIF DI SD IT BIAS AS SSALAM KELAS IV - Aditya Nur Rahma; Tauhid Mubarok (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Learning is a process of individual efforts to obtain new behavioral changes as a result of experiences interacting with the environment. This research aims to discuss how to improve Akidah Akhlak learning outcomes in SD IT Bias Assalam Class IV. Moral beliefs are a foundation that plays an important role in shaping the personality of every Muslim. The method used is a qualitative research method. The data collection techniques used are observation, tests, interviews, documentation and descriptive data. After conducting research in Class 4 of SD IT Bias Assalam Tegal, South Digal City, students who used interactive learning methods experienced an increase in learning achievement, namely the average in the previous cycle was 73.8 with a completion rate of 30%, and the average in the first cycle is 75.2, completeness level 50%, cycle II average 76.5 and completeness 70%, cycle III average 85.7 and completeness 100%. Therefore, it can be concluded that the application of interactive learning methods can improve student learning outcomes at SD IT Bias Assalam Tegal, South Tegal City.